Reduction Of Cyanate To Cyanide In Cyanidation Tailings Under Reducing Environments - H. K. Lin (Society for Mining, Metallurgy & Exploration, 2008)
Residual cyanide in cyanidation tailings can be detoxified by its oxidation to cyanate, as in the Inco and Degussa processes. However, cyanate, the product of detoxification and other oxidation processes, may be reduced to cyanide in reducing environments, e.g., deepwater discharge of cyanidation tailings. This study shows that the reduc-tion of cyanate to cyanide occurs and that the reduction rate increases with decreasing solution redox potential. Solutions with lower pH favor the reduction rate. No significant difference was observed between the results of tests prepared with distilled water and seawater, and the presence of cyanidation solid tailings does not show an effect on the reduction. Because cyanate can be reduced to toxic cyanide, causing environmental concerns, the deepwater discharges of cyanidation tailings must be handled carefully.